Proyecto De Negocio Internacional Para La Exportación De Huevos Tipo Aa Desde Colombia Hasta La Ciudad De Berlín, Alemania (2024)
This thesis focusses on an international business project which will evaluate and analize the viability of exporting eggs into the market of Berlin, Germany. This project arises due to the installed capacity in a company from Meta department of Colombia and the oportunity to expand into new markets since eggs are widely consumed worldwide due to their varieties and easy preparation plus of course the nutritional value, vitamines and protein that it brings to the human body.